Conceptualizing a Priestly World: Past, Present, and Future in Hellenistic Babylon - Céline Debourse; Michael Jursa (Religions)
In a world that grew increasingly more foreign, the Marduk priests of Hellenistic Babylon endeavored to maintain their ancient traditions and beliefs. Central to their worldview was the idea that the gods decided the fates of the land and that to ensure their benevolence, temple worship was not only necessary but the primary raison d’être of the priests themselves. However, foreign rule posed significant challenges to the traditional Babylonian temple cult. In this paper, we argue that in response, the Babylonian priests developed new discursive paradigms that sought to influence their future by reinterpreting their past in light of their present. On the one hand, this took the form of traditional models of cuneiform literacy and was developed in texts dealing with history and ritual (Late Babylonian Priestly Literature). On the other hand, the priesthood advanced a new intellectual model that expanded beyond the scope of traditional knowledge and took the form of a mathematical-astronomical paradigm. While there is an apparent tension between both paradigms, we posit that their overarching objectives remained the same: understanding the divinely determined future through the past (and present) and influencing it by ritual action directed towards the divine. Studying this Babylonian model is valuable for understanding parallel epistemological and discursive processes taking place in other ancient Near Eastern temple communities that faced similar challenges under foreign imperial rule.